IMPACT OF PUSLED ELECTROMAGNETIC FIELD ON PROTEINE IN SEED OF SOYBEAN - Đukić, Vojin H; Miladinov, Zlatica J; Dozet, Gordana K; Miladinović, Jegor A; Ranđelović, Predrag; Kandelinskaja , Olga (Journal of Agricultural Sciences (Belgrade), 2020)
The aim of this study was to investigate how pulsed electromagnetic fields (PEMF) affect the protein yield of soybean seeds depending on the year, exposure time and frequency. The field trials were conducted in the experimental field of the Institute of Field and Vegetable Crops in Novi Sad, Serbia. For this research, the seeds of a medium-sized variety Valjevka exposed to a pulsed electromagnetic field (PEMF) using a pulse generator and a strip applicator were used. A low frequency pulsed electromagnetic field (16, 24, 30, 72 Hz) was used at the exposure times of 0, 30, 60, and 90 minutes. The results of the research show that the application of this method can increase the yield of protein in soybean seeds by up to 20%, which is a significant increase and a good basis for this measure to be used, especially in organic production, where the use of seed treatment agents is very restrictive. However, this measure can also have an inhibitory effect if an adverse combination of exposure time and frequency strength is selected. Keywords: Proteins, Pulsed electromagnetic field, Soybeans.